ENDOVASCULAR TREATMENT OF CAROTID ATHEROSCLEROSIS: CONCERNS AND PERSPECTIVES - T. V. Tvorogova; E. S. Bulgakova; F. B. Shukurov; B. A. Rudenko; O. M. Drapkina; A. S. Shanoyan (Рациональная фармакотерапия в кардиологии)
Stroke is one of the most frequent causes  of death and permanent disability among adults. The majority of ischemic strokes  are due to atherosclerotic plaque in the internal carotid artery. Carotid endarterectomy is more effective than medical management in the prevention of stroke in patients with carotid artery stenosis. Carotid artery stenting, a less invasive revascularization strategy than  endarterectomy, is also wide-spread but it is associated with more periprocedural complications. Knowledge of risk factors of these  complications may impact treatment decisions for the individual patient, but these factors have not been extensively studied.